The visual anthropologist in the digital library: From filmstrips to Salient stills and back to Barthes - Zeitlyn, D (John Wiley and Sons, 2006)
Advances in digital image processing lead to ways of representing images and image-collections that approach the linguistic properties of concision and summary. However, important logical differences remain. Indexing is a form of summary representation with problematic application to visual material. "Salient stills " and "film strips " as representations of video clips have been suggested as solutions. Yet problems with abstract nonverbal representations return us to the theoretical stance of Walter Benjamin and Roland Barthes: images are approached textually. © 2006 by the American Anthropological Association.